2018
DOI: 10.1142/s0218126619300022
|View full text |Cite
|
Sign up to set email alerts
|

A Short Review of Security-Aware Techniques in Real-Time Embedded Systems

Abstract: With the rapid development of embedded systems, users and services have been greatly facilitated while also experiencing security threats as a result of cyber-attacks and system vulnerabilities. Currently, the real-time embedded system (RTES) focus is to deal with these security issues. In this paper, we introduce a short review of security-aware techniques for RTES. We mainly discuss two common approaches to improve the security of RTESs. The first approach is achieved by exploring specific attacks. The secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…In other words, if the capabilities of ESs increase in terms of points of connection and input units, then attack surfaces increase, thereby increasing the probability that the system is hacked. [26] ES design principles [20] ESs' security from new dimension [27] Security-aware and real-time ES [28] Hardware enhancement of ES [29] Cybersecurity for cyber-physical system [22] IoT and security measurements [30] Taxonomy of detection approaches [31] Data privacy and policy problems survey [13] Security requirements and challenges in IoT [32] Challenges, threats and solutions of IoT [33] A roadmap for security challenges in the IoT [7] A taxonomy of threats, vulnerabilities and attacks. [34] A survey of cyber-physical systems security [35] Security framework for IoT…”
Section: A Security Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, if the capabilities of ESs increase in terms of points of connection and input units, then attack surfaces increase, thereby increasing the probability that the system is hacked. [26] ES design principles [20] ESs' security from new dimension [27] Security-aware and real-time ES [28] Hardware enhancement of ES [29] Cybersecurity for cyber-physical system [22] IoT and security measurements [30] Taxonomy of detection approaches [31] Data privacy and policy problems survey [13] Security requirements and challenges in IoT [32] Challenges, threats and solutions of IoT [33] A roadmap for security challenges in the IoT [7] A taxonomy of threats, vulnerabilities and attacks. [34] A survey of cyber-physical systems security [35] Security framework for IoT…”
Section: A Security Problemsmentioning
confidence: 99%
“…It is also worth mentioning the criticality of a real-time embedded system (RTES). Specific security countermeasures for RTES can be implemented in two stages: (i) identify specific attacks that could threaten the systems; and (ii) implement security-guaranteed services, overcoming the challenges of real-time performance and energy consumption [27]. The study in [88] showed how security measures could be circumvented in different platforms.…”
Section: B Security Countermeasures Of Essmentioning
confidence: 99%
See 1 more Smart Citation
“…Constrained resources hinder the implementation of advanced encryption (ciphers and deciphers), intrusion detection systems (IDSs), and other advanced security solutions. Most of the sophisticated security countermeasures require intensive computing and inevitably consume more energy, as these solutions are power-hungry [17]. Also, Riahi Sfar et al addressed the issue of existing cryptographic algorithms, which require more resources in terms of processing power, memory, and energy, which may be unavailable in limited resource SoCs [18] due to the systems' nature.…”
Section: A Embedded Systems and Cybersecurity Challengesmentioning
confidence: 99%
“…Neglecting security countermeasures at the early stages of ES design increases the number of unprotected entry points, which can result in unauthorized access to the system. As many ESs are battery-powered, and as long as the enhancement of security solutions might sacrifice part of the power sources, it is crucial to at minimum reduce the amount of power consumption with lightweight and efficient solutions [17]. Running robust encryption on ESs with their constrained resources is a critical challenge [19], [20].…”
Section: A Embedded Systems and Cybersecurity Challengesmentioning
confidence: 99%